E2EE enhanced patient-centric blockchain-based system for EHR management - Haddad, Alaa; Habaebi, Mohamed Hadi; Elsheikh, Elfatih A A; Islam, Md Rafiqul; Ahmad Zabidi, Suriza; M Suliman, Fakher Eldin (Public Library of Science, 2024)
To secure sensitive medical records in the healthcare clouds, this paper proposes an Endto- End Encryption (E2EE) to enhance a patient-centric blockchain-based system for electronic health record (EHR) management. The suggested system with a focus on the patient enables individuals to oversee their medical records within various involved parties by authorizing or withdrawing permission for access to their records. Utilizing the inter-planetary file system (IPFS) for record storage is chosen due to its decentralized nature and its ability to guarantee the unchangeability of records. Then an E2EE enhancement maintains the medical data integrity using dual level-Hybrid encryption: symmetric Advanced Encryption Standard (AES) and asymmetric Elliptic Curve Cryptography (ECC) cryptographic techniques. The proposed system is implemented using the Ethereum blockchain system for EHR data sharing and integration utilizing a web-based interface for the patient and all users to initiate the EHR sharing transactions over the IPFS cloud. The proposed system performance is evaluated in a working system prototype. For different file sizes between 512 KB to 100 MB, the performance metrics used to evaluate the proposed system were the time consumed for generating key, encryption, and decryption. The results demonstrate the proposed system’s superiority over other cutting-edge systems and its practical ability to share secure health data in cloud environments.